BRCA1 mutations in a selected series of breast/ovarian cancer patients. Issue 9 (September 1996) - Garvin, A M; Spycher, M; Häner, M; Torhorst, J; Müller, H; Herrmann, R; Rochlitz, C; Weber, W; Scott, R J
Abstract : Germline mutations in the BRCA1 gene have been associated with familial breast/ ovarian cancer in large families showing high penetrance of the disease. Little is known, however, about the contribution of BRCA1 mutations to breast/ovarian cancer in small families with few affected members or in isolated early onset cases. Therefore we examined the BRCA1 gene in 63 breast/ovarian cancer patients who either came from small families with as few as one affected first degree relative, or in patients who had no family history but had developed breast cancer under 40 years of age. Using the protein truncation test, we were able to identify three unique BRCA1 germline mutations (4.8%). Two of the probands had only one affected first degree and several second degree relatives and the third had three affected first degree relatives including two sisters who, when tested, were also found to carry the mutation. There was no family history of ovarian cancer in any of the three families.